Lithium iron phosphate positive electrode material and preparation method thereof, positive electrode plate and lithium battery
By introducing a carbon cladding layer into the lithium iron phosphate positive electrode material and optimizing the crystal structure, the problem of low lithium ion diffusion rate is solved, and the electrochemical performance improvement and multi-performance optimization of lithium ion batteries are achieved.
Patent Information
- Application Number
- CN202510287890.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The lithium ion diffusion rate in lithium iron phosphate positive electrode materials is low, resulting in poor electrochemical performance under high current density.
By introducing a carbon cladding layer into the lithium iron phosphate positive electrode material, and by optimizing the crystal structure, the reverse position defect of the iron lithium is reduced, and the quality of the lithium ion diffusion channel is improved.
The lithium ion diffusion rate is improved, the electrode reaction kinetics is improved, and the lithium ion battery has excellent rate performance, low temperature resistance and low polarization degree.
Smart Images

Figure CN119812318A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium battery. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP for short) is an important cathode material for lithium-ion batteries. It stands out in many application fields due to its excellent safety, long cycle life and low cost. Lithium iron phosphate is composed of PO4 tetrahedron, LiO6 octahedron and FeO6 octahedron connected by common edges and arranged alternately to form a stable crystal structure to adapt to long-term repeated insertion and extraction of lithium ions. However, this stable crystal structure will hinder Li + transmission, making Li + In lithium iron phosphate crystals, the insertion / extraction usually occurs along one-dimensional direction. The iron-lithium antisite defects existing in this direction hinder the transmission of lithium ions, resulting in a low lithium ion diffusion rate. Therefore, LiFePO4 is difficult to exhibit excellent electrochemical performance at high current density.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The purpose of the present application is to provide a lithium iron phosphate positive electrode material with high lithium ion diffusion rate and electrode reaction kinetics, so that the battery prepared by the lithium iron phosphate positive electrode material has excellent rate performance, low temperature resistance and low polarization degree.
[0005] In order to achieve the above object, the present invention is achieved as follows: In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, comprising a lithium iron phosphate matrix and a carbon coating layer located on the surface of the lithium iron phosphate matrix.
[0006] The crystal structure of the lithium iron phosphate cathode material ×10000, unit is nm -1 , α satisfies 0.15nm -1 ≤α≤4.5nm -1 ; In the formula, represents the percentage of lithium iron antisite defects in the lithium iron phosphate positive electrode material, D (020) represents the grain size of the (020) crystal plane of the lithium iron phosphate positive electrode material, in nm. I (200) represents the peak intensity of the (200) characteristic diffraction peak in the X-ray diffraction spectrum of the lithium iron phosphate positive electrode material, I (020)It represents the peak intensity of the (020) characteristic diffraction peak in the X-ray diffraction spectrum of the lithium iron phosphate positive electrode material.
[0007] In an optional embodiment, the lithium iron phosphate positive electrode material satisfies at least one of the following characteristics (1)-(4): Feature (1): The crystal structure degree α of the lithium iron phosphate positive electrode material satisfies 0.5nm -1 ≤α≤1.1nm -1 ; Feature (2): The lithium iron phosphate positive electrode material ≤5%; Feature (3): D of the lithium iron phosphate positive electrode material (020) The value ranges from 35nm to 85nm; Feature (4): The lithium iron phosphate positive electrode material The value is 0.25-0.45.
[0008] In an optional embodiment, the general structural formula of the lithium iron phosphate matrix is Li 1-x J x Fe 1-y M y (PO 4-z )Q z ; Wherein, J is selected from at least one of Na and Mg; M is at least one selected from Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; Q is selected from at least one of F, S, N and Cl; 0≤x≤0.1, 0≤y≤0.1 and 0≤z≤0.1.
[0009] In a second aspect, the present invention provides a method for preparing a lithium iron phosphate positive electrode material according to any one of the aforementioned embodiments, comprising the following steps: Mixing a crystal form regulator and a metal salt in a macromolecular solution to form a first solution, adjusting the pH of the first solution to obtain a gel; and soaking the gel in a solution of the metal salt to obtain an iron source carrier; The iron source carrier, the lithium source and the phosphorus source are mixed in water to obtain a mixture; the mixture is subjected to a hydrothermal reaction and solid-liquid separation to obtain a lithium iron phosphate precursor; The lithium iron phosphate precursor and the carbon source are mixed and calcined under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.
[0010] In an optional embodiment, the metal salt includes an iron salt and an M salt, and the molar ratio of the iron element in the iron salt to the M element in the M salt is 1:0-0.11. The iron salt is a soluble salt of divalent iron, including at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate and ferrous acetate. The M salt is a water-soluble salt of the M element, and the M element includes at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y.
[0011] In an optional embodiment, the process for preparing the iron source carrier satisfies at least one of the following features (5)-(11): Feature (5): The percentage content of the macromolecule in the first solution is 1wt%-30wt%; Feature (6): The mass ratio of the macromolecule, the crystal form regulator and the metal salt in the first solution is 1:0.05-0.3:0.05-0.5; Feature (7): The macromolecule comprises at least one of chitosan, carboxymethyl chitosan, tannic acid, gelatin and aminoethyl-β-cyclodextrin, and the crystal form regulator comprises at least one of ethylene glycol, polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and diethylene glycol; Feature (8): The pH adjustment refers to adjusting the pH of the first solution to 7.0-7.5; Feature (9): The concentration of divalent iron ions in the metal salt solution is 0.1 mol / L-1.0 mol / L; Feature (10): The solid-to-liquid ratio of the gel and the metal salt solution is 1 g: 100 mL-500 mL, and the soaking time is 10 min-30 min; Feature (11): The first solution and / or the metal salt solution also includes an antioxidant, the antioxidant includes ascorbic acid, and the molar ratio of the antioxidant to the iron element in the first solution and / or the metal salt solution is 0.1-0.3:1.
[0012] In an optional embodiment, the preparation method satisfies at least one of the following features (12)-(15): Feature (12): The lithium source comprises at least one of lithium hydroxide, lithium chloride and lithium acetate, and the concentration of the lithium source in the mixture is 0.8 mol / L-2.5 mol / L; Feature (13): The mixture further includes a doping source, which includes a metal doping source and / or a non-metal doping source; the metal doping source is a J source, which is a water-soluble compound containing at least one of the elements Na and Mg; the non-metal doping source is a Q source, which is a water-soluble compound containing at least one of the elements F, S, N and Cl; Feature (14): The pH of the mixture is 2.0-6.0; Feature (15): The reaction temperature of the hydrothermal reaction is 140°C-240°C, and the reaction time is 5h-20h.
[0013] In an optional embodiment, the preparation method satisfies at least one of the following features (16)-(18): Feature (16): The carbon source comprises at least one of sucrose, glucose, starch, polyethylene glycol, phenolic resin, cellulose and citric acid, and the mass of the carbon source is 0.1%-3% of the mass of the lithium iron phosphate precursor; Feature (17): The inert atmosphere comprises at least one of nitrogen, helium and argon; Feature (18): The calcination temperature is 500°C-800°C, and the calcination time is 4h-14h.
[0014] In a third aspect, the present invention provides a positive electrode plate, comprising the lithium iron phosphate positive electrode material in any one of the aforementioned embodiments or the lithium iron phosphate positive electrode material prepared by any one of the preparation methods in the aforementioned embodiments.
[0015] In a fourth aspect, the present invention provides a lithium battery comprising the positive electrode sheet of the aforementioned embodiment.
[0016] The present invention has the following beneficial effects: (1) The present invention optimizes the crystal structure of the lithium iron phosphate positive electrode material, so that the activation energy of the lithium ion extraction and insertion reaction in the lithium iron phosphate positive electrode material is low and the lithium diffusion rate is high, so it has excellent electrode reaction kinetics. Furthermore, the corresponding lithium ion battery has excellent rate performance, low temperature resistance and low polarization degree.
[0017] (2) The iron source carrier prepared in the present invention slowly releases Fe during the hydrothermal reaction. 2+ and crystal modifiers, on the one hand, reduce Fe 2+ On the other hand, the crystal form regulator is slowly released during the growth stage of lithium iron phosphate to induce the crystal to grow in a suitable preferred orientation, so that the obtained lithium iron phosphate positive electrode material has excellent electrode reaction kinetics and high tap density. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1A refined X-ray diffraction pattern of the lithium iron phosphate positive electrode material provided in Example 6; Figure 2 A transmission electron microscope image of the lithium iron phosphate positive electrode material provided in Example 7; Figure 3 The cyclic voltammetry curves (-15°C) of lithium iron phosphate positive electrode materials are shown in Figure 5, wherein (a) is the lithium iron phosphate positive electrode material provided in Example 6, and (b) is the lithium iron phosphate positive electrode material provided in Comparative Example 2. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.
[0021] In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0022] In the description of the embodiments of the present application, the terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order, or primary and secondary relationship of the indicated technical features. The term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone.
[0023] For simplicity, the present invention specifically discloses some numerical ranges, and various numerical ranges can be combined with each other to form corresponding embodiments. The endpoints and any value of the scope disclosed in the present invention are not limited to this accurate scope or value, and these scopes or values should be understood as comprising values close to these scopes or values. For numerical range, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between the separate point value, can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.
[0024] Unless otherwise specified, the terms used in the present invention have the commonly understood meanings that are generally understood by those skilled in the art.
[0025] Due to its olivine crystal structure, lithium iron phosphate positive electrode materials can only diffuse lithium ions along a one-dimensional channel. The iron-lithium anti-site defects existing in this channel seriously hinder the diffusion of lithium ions, resulting in a low lithium ion diffusion rate and poor electrode reaction kinetics. Therefore, nano-sizing is often used in this field to prepare small-sized lithium iron phosphate particles to shorten the lithium ion diffusion distance, but nano-sizing is usually accompanied by an unstable reaction state and easily increases iron-lithium anti-site defects. Alternatively, the lithium ion diffusion channel can be shortened by inducing the preferred orientation growth of lithium iron phosphate crystals, but the morphology of lithium iron phosphate will present a plate-like or flaky structure, and the tap density will be reduced, which will in turn affect the discharge specific capacity and energy density.
[0026] After extensive experiments and research, the inventors of the present application have discovered a technical solution that enables lithium iron phosphate positive electrode materials to have both excellent electrode reaction kinetics and high tap density, so that lithium-ion batteries have both excellent rate performance, low temperature resistance and low polarization degree.
[0027] The present invention provides a lithium iron phosphate positive electrode material, comprising a lithium iron phosphate matrix and a carbon coating layer located on the surface of the lithium iron phosphate matrix. ×10000, unit is nm -1 , α satisfies 0.15nm -1 ≤α≤4.5nm -1 ; In the formula, Indicates the percentage of lithium iron anti-site defects in lithium iron phosphate positive electrode materials (%); D (020) Represents the grain size of the (020) crystal plane of lithium iron phosphate positive electrode material, in nm; I (200) I represents the peak intensity of the (200) characteristic diffraction peak in the X-ray diffraction spectrum of the lithium iron phosphate positive electrode material; (020) Represents the peak intensity of the (020) characteristic diffraction peak in the X-ray diffraction pattern of lithium iron phosphate positive electrode material.
[0028] The crystal structure degree α of the lithium iron phosphate positive electrode material of the present invention is 0.15nm -1 -4.5nm -1 , for example, it can be 0.15nm -1 , 0.5nm -1 , 1.0nm -1 , 2.0nm -1 、3.0nm -1 、4.0nm -1 、4.5nm -1 Any one of them or the range between any two.
[0029] It should be noted that the iron-lithium antisite defect is an inherent lattice dislocation phenomenon, which means that iron ions occupy the position that should be occupied by lithium ions. The existence of this defect will reduce Li + The storage points seriously hinder or even cut off the diffusion of lithium ions in the lithium iron phosphate positive electrode material, increase the activation energy of the lithium ion extraction and embedding reaction, and cause a significant reduction in the electrochemical performance.
[0030] D (020) is the grain size of the lithium iron phosphate cathode material in the (020) crystal plane direction. In the lithium iron phosphate cathode material, due to Li + The activation energy required for transmission along the b-axis is the lowest, so that the lithium ions of the lithium iron phosphate positive electrode material tend to diffuse along the one-dimensional channel in the b-axis direction (perpendicular to the (020) crystal plane direction). The smaller the size of the crystal in this direction, the shorter the distance of the lithium ion diffusion channel, which is more conducive to the realization of high-rate performance.
[0031] I (200) and I (020) They are respectively the peak intensities of the characteristic diffraction peak of the (200) crystal plane and the characteristic diffraction peak of the (020) crystal plane in the X-ray diffraction pattern of the lithium iron phosphate positive electrode material. The ratio reflects the oriented growth mode of lithium iron phosphate cathode material. The smaller the value, the shorter the length of the lithium iron phosphate cathode material along the ac plane. The crystal orientation of lithium iron phosphate is in the a, b and c axes. + The activation energy required for transmission along the b-axis (perpendicular to the (020) crystal plane) is the lowest, making the lithium ions of the lithium iron phosphate cathode material more inclined to diffuse along the b-axis. In this transmission mode, the b-axis is the lithium ion diffusion channel and is perpendicular to the ac plane formed by the a-axis and the c-axis. The larger the ac plane is, the more lithium ion diffusion channels there are. The peak intensity ratio of the characteristic diffraction peaks of the crystal plane can reflect the relative content of the crystal plane, I (020) is the diffraction peak intensity of the ac crystal plane, I (200) is the diffraction peak intensity of the bc crystal plane, The smaller the value, the higher the relative content of ac crystal plane, that is, the crystal orientation of lithium iron phosphate is preferentially oriented along the ac plane, that is, the lithium ion diffusion channels along the b axis are relatively short and numerous. + The transmission distance is shortened and the transmission efficiency is improved.
[0032] In summary, the iron lithium antisite defect, D (020) ,I (200) and I (020) All of them will affect the diffusion of lithium ions. Through the study of the above parameters, the crystal structure degree is proposed. , the crystal structure ×10000 comprehensively reflects the quality of the lithium ion diffusion channel of the lithium iron phosphate positive electrode material. The better the quality, the faster the lithium ion diffusion and the better the electrode reaction kinetics. The value range is 0.15nm -1 -4.5nm -1 The lithium iron phosphate cathode material has a high-quality lithium ion diffusion channel, which has less obstacles and has a suitable number and length, so that the lithium iron phosphate cathode material has a high tap density and exhibits excellent electrode reaction kinetics. Furthermore, the corresponding lithium-ion battery has excellent rate performance, low temperature resistance and low polarization degree.
[0033] In some embodiments, the crystal structure degree α satisfies 0.5 nm -1 ≤α≤1.1nm -1 The lithium iron phosphate positive electrode material whose crystal structure degree α meets this range has better electrochemical performance.
[0034] In some embodiments, The value is ≤5%.
[0035] In some embodiments, D (020) The value of D is 35nm-85nm, for example, it can be any one of 35nm, 45nm, 55nm, 65nm, 75nm and 85nm, or a range between any two of them. (020) If it is too small, the tap density of the lithium iron phosphate positive electrode material will be reduced, affecting the discharge specific capacity. At the same time, it will also reduce the mechanical strength of the lithium iron phosphate positive electrode material. The crystal structure will easily collapse during repeated charge and discharge, and the cycle performance will be reduced.
[0036] In some embodiments, The value of can be 0.25-0.45, for example, it can be any one of 0.25, 0.30, 0.35, 0.40 and 0.45 or a range between any two of them. If the value is too small, it means that the length of the lithium iron phosphate positive electrode material along the b-axis is too short, making the morphology of the lithium iron phosphate positive electrode material plate-like or sheet-like, affecting the tap density and compaction density, and further affecting the specific capacity and energy density. If it is too large, it means that the length of the lithium iron phosphate positive electrode material along the b-axis is too long, that is, the lithium ion diffusion channel is too long, which affects the speed of lithium ion diffusion and thus affects the rate performance.
[0037] In some embodiments, the lithium iron phosphate matrix has the general structural formula Li 1-x J x Fe 1-y M y (PO 4-z )Qz ; In the formula, J is selected from at least one of Na and Mg, and J can be any one or more of the above elements; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, and M can be any one or more of the above elements; Q is selected from at least one of F, S, N and Cl, and Q can be any one or more of the above elements. The values of the subscripts x, y, and z in the general formula are as follows: 0≤x≤0.1, 0≤y≤0.1, and 0≤z≤0.1, x, y, and z can be equal or different, and can independently be 0.00, 0.03, 0.05, 0.08, 0.10, etc.
[0038] The present invention provides a method for preparing the above-mentioned lithium iron phosphate positive electrode material, but the preparation method is not limited thereto. The preparation method comprises the following steps: S1. Mixing a crystal form regulator and a metal salt in a macromolecular solution to form a first solution, adjusting the pH of the first solution to obtain a gel; and immersing the gel in a metal salt solution to obtain an iron source carrier.
[0039] S2. Mixing an iron source carrier, a lithium source and a phosphorus source in water to obtain a mixture; subjecting the mixture to a hydrothermal reaction and solid-liquid separation to obtain a lithium iron phosphate precursor.
[0040] S3. Mixing the lithium iron phosphate precursor and the carbon source and calcining them under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.
[0041] The present invention prepares the crystal form regulator and Fe by gel method. 2+ The iron source carrier is used to combine the functional groups of macromolecules and crystal modifiers with metal ions (mainly Fe 2+ ) coordinate to form a complex, and the macromolecules and / or crystal modifiers interact with each other through hydrogen bonds, so that the macromolecules, crystal modifiers and metal ions form a gel cross-linked by physical cross-linking. The gel is immersed in a metal salt solution for reinforcement, and further loaded with metal ions to obtain a metal source carrier. Since the metal source in the metal source carrier is mainly Fe 2+ Source, for better expression, the present invention uses iron source carrier to replace metal source carrier throughout the text. Part of the iron source carrier Fe 2+ The functional groups of the macromolecules and crystal modifiers coordinate to form the skeleton structure of the gel to ensure the structural stability of the gel; the other part of Fe 2+ During soaking reinforcement, it is loaded in the gel and has a greater degree of freedom of movement than the Fe 2+ , forming and releasing Fe 2+ Iron source sustained-release carrier with different release rates.
[0042] The iron source carrier, lithium source and phosphorus source are mixed in water and subjected to hydrothermal reaction to obtain a lithium iron phosphate precursor. 2+ Prioritized release, reacting with lithium and phosphorus sources at high temperature and high pressure to form nuclei and grow; due to the slow release of Fe by the iron source carrier 2+ , making Fe 2+ The diffusion rate is higher than that of Li + Slow down, Li + Will be better than Fe 2+ First, it is introduced into the crystal structure to occupy the position of lithium, avoiding the generation of iron-lithium anti-position. In the later stage of the reaction, as the hydrothermal reaction proceeds, the Fe 2+ The release begins, the iron source carrier gradually collapses, the macromolecules and the crystal form regulator are dispersed into the solvent, and the crystal form regulator forms hydrogen bonds with the oxygen atoms on the (020) crystal plane of LiFePO4 in the b-axis direction, inhibiting the growth of the crystal plane along the b-axis direction, and promoting the growth of the crystal along the non-inhibited crystal plane direction, thereby inducing the growth of lithium iron phosphate into a crystal with an exposed (020) crystal plane, shortening the lithium ion diffusion channel. Because the crystal form regulator is gradually released in the late stage of the hydrothermal reaction, the lithium iron phosphate crystal has already shown a spherical morphology of a certain size. At this stage, the crystal form regulation can avoid the appearance of ultra-short b-axis rod-shaped and sheet-shaped crystal morphology, so that the lithium iron phosphate crystal maintains a spherical morphology to ensure good tap density and compaction density.
[0043] In some embodiments, the metal salt includes an iron salt and an M salt, the molar ratio of the iron element in the iron salt to the M element in the M salt is 1:0-0.11, the iron salt is a soluble salt of divalent iron, including at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate and ferrous acetate; the M salt is a water-soluble salt of the M element, and the M element includes at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y. When the molar ratio of the iron element to the M element is 1:0, it means that the metal salt contains only the iron salt.
[0044] In some embodiments, the process of preparing the iron source carrier includes performing the process under an inert atmosphere. Preparing the iron source carrier under an inert atmosphere can effectively prevent the oxidation of divalent iron to trivalent iron.
[0045] In some embodiments, the percentage content of the macromolecule in the first solution is 1 wt%-30 wt%, for example, it can be any one of 1 wt%, 5 wt%, 10 wt%, 20 wt% and 30 wt% or a range between any two of them.
[0046] In some embodiments, the mass ratio of the macromolecule, the crystal form modifier and the metal salt in the first solution is 1:0.05-0.3:0.05-0.5, for example, it can be any one of 1:0.05:0.05, 1:0.05:0.5, 1:0.3:0.05, 1:0.3:0.5 and 1:0.2:0.3 or a range value between any two of them. The mass ratio of the macromolecule, the crystal form modifier and the metal salt can affect the crosslinking density of the gel, and thus affect the mechanical strength and decomposition rate of the gel.
[0047] In some embodiments, the macromolecule includes at least one of chitosan, carboxymethyl chitosan, tannic acid, gelatin and aminoethyl-β-cyclodextrin, and the crystal modifier includes at least one of ethylene glycol, polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and diethylene glycol.
[0048] In some embodiments, the pH of the first solution is adjusted to 7.0-7.5 to obtain a gel, for example, the pH range can be any one of 7.0, 7.1, 7.2, 7.3, 7.4 and 7.5 or a range between any two of them. The above macromolecules contain a large number of hydrogen-containing active groups, and adjusting the pH of the first solution to 7.0-7.5 is conducive to the deprotonation of the hydrogen-containing active groups, making it easier to coordinate with metal ions and promoting physical cross-linking to form a gel.
[0049] In some embodiments, the solution of metal salt is a mixed aqueous solution of metal salts, and the concentration of divalent iron ions in the solution of metal salt is 0.1 mol / L-1.0 mol / L, for example, it can be any one of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L and 1.0 mol / L or a range value between any two of them.
[0050] In some embodiments, the solid-to-liquid ratio of the gel and the metal salt solution is 1g:100mL-500mL, for example, it can be any one of 1g:100mL, 1g:300mL and 1g:500mL, or a range value between any two of them; the soaking time is 10min-30min, for example, it can be any one of 10min, 20min and 30min, or a range value between any two of them.
[0051] In some embodiments, the first solution and / or the metal salt solution further comprises an antioxidant, the antioxidant comprises ascorbic acid, and the molar ratio of the antioxidant to the iron element in the first solution and / or the metal salt solution is 0.1-0.3:1, for example, it can be any one of 0.1:1, 0.2:1 and 0.3:1 or a range value between any two thereof. Adding an antioxidant can prevent the divalent iron from being oxidized to trivalent iron.
[0052] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium chloride and lithium acetate, and the concentration of the lithium source in the mixture is 0.8 mol / L-2.5 mol / L, for example, it can be any one of 0.8 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L and 2.5 mol / L, or a range value between any two of them.
[0053] In some embodiments, the mixture also includes a doping source, which includes a metal doping source and / or a non-metallic doping source; the metal doping source is a J source, which is a water-soluble compound containing at least one of Na and Mg elements; the non-metallic doping source is a Q source, which is a water-soluble compound containing at least one of F, S, N and Cl elements.
[0054] In some embodiments, the pH of the mixture is 2.0-6.0, for example, any one of 2.0, 3.0, 4.0, 5.0 and 6.0 or a range between any two of them. The pH of the mixture will affect the sustained release rate of the iron source carrier. The lower the pH of the mixture, the faster the iron source carrier releases Fe. 2+ The faster the rate, the higher the saturation of the hydrothermal reaction system, and the faster the nucleation and growth of lithium iron phosphate crystals. In some cases, the pH value of the hydrothermal reaction system can be regulated by adding a common acidic regulator such as hydrochloric acid to ensure that it is within the set range.
[0055] In some embodiments, the reaction temperature of the hydrothermal reaction is 140°C-240°C, for example, it can be any one of 140°C, 160°C, 180°C, 200°C and 240°C, or a range value between any two of them; the reaction time is 5h-20h, for example, it can be any one of 5h, 10h, 15h and 20h, or a range value between any two of them.
[0056] In some embodiments, the carbon source includes at least one of sucrose, glucose, starch, polyethylene glycol, phenolic resin, cellulose and citric acid. The mass of the carbon source is 0.1%-3% of the mass of the lithium iron phosphate precursor, for example, it can be any one of 0.1%, 0.5%, 1.0%, 1.5%, 2% and 3%, or a range value between any two. Adding the carbon source during the calcination process can form a carbon coating layer to improve the conductivity of the lithium iron phosphate positive electrode material.
[0057] In some embodiments, the inert atmosphere includes at least one of nitrogen, helium, and argon.
[0058] In some embodiments, the calcination temperature is 500°C-800°C, for example, it can be any one of 500°C, 600°C, 700°C and 800°C, or a range value between any two of them; the calcination time is 4h-14h, for example, it can be any one of 4h, 8h, 10h, 12h and 14h, or a range value between any two of them.
[0059] An embodiment of the present invention also provides a positive electrode plate, including the above-mentioned lithium iron phosphate positive electrode material, and may also include a positive electrode current collector, a positive electrode active coating is formed on at least one surface of the positive electrode current collector, and the lithium iron phosphate positive electrode material exists in the positive electrode active coating as a positive electrode active material.
[0060] An embodiment of the present invention further provides a lithium battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, a separator, etc. to form a complete battery structure with good electrochemical performance.
[0061] Specifically, the specific types of the negative electrode sheet, electrolyte, and separator are not limited. The lithium battery can be in the form of a secondary battery. During the charge and discharge process of the secondary battery, active ions are intercalated and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet.
[0062] In other embodiments, the battery may not be in the form of a secondary battery, but may be in the form of a battery module, a battery pack, etc.
[0063] The embodiment of the present invention provides a device, including the above-mentioned secondary battery, battery module or battery pack, which can be used as a power source of the device or as an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. In a nitrogen atmosphere, polyethylene glycol and ferrous sulfate are heated and mixed in an acetic acid aqueous solution of chitosan at 45°C to form a first solution, the pH of the first solution is adjusted to 7.5, and the solution is allowed to stand to obtain a gel; the gel is placed in a 0.3 mol / L ferrous sulfate solution at a solid-liquid ratio of 1 g:200 mL and immersed for 10 minutes to obtain an iron source carrier.
[0066] Among them, the concentration of acetic acid in the acetic acid aqueous solution is 1.5wt%, and the concentration of chitosan in the first solution is 2wt%; the mass ratio of chitosan, polyethylene glycol and ferrous sulfate in the first solution is 1:0.2:0.3; the first solution and the ferrous sulfate solution contain ascorbic acid, and the molar ratio of ascorbic acid to the iron element in the first solution and the ferrous sulfate solution is 0.2:1.
[0067] S2. Mix the iron source carrier, lithium hydroxide and phosphoric acid in water, adjust the pH to 3.5 to obtain a mixture, react the mixture in a reactor at 170° C. for 15 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0068] The molar ratio of P:Li:Fe in the mixture is 1:1.3:1, and the concentration of lithium hydroxide in the mixture is 1.0 mol / L.
[0069] S3, grinding and mixing the lithium iron phosphate precursor and glucose, spray drying, and calcining at 680° C. for 9 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0070] Among them, the mass of glucose is 2.2% of the mass of the lithium iron phosphate precursor.
[0071] Example 2 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. In a nitrogen atmosphere, polyvinyl alcohol and a metal salt are mixed in an aqueous solution of gelatin to form a first solution, the pH of the first solution is adjusted to 7.2, and the solution is allowed to stand to obtain a gel; the gel is placed in a solution of a metal salt at a solid-liquid ratio of 1 g:500 mL and immersed for 30 minutes to obtain an iron source carrier.
[0072] Among them, the metal salt is a mixture of ferrous chloride and cobalt acetate, and the molar ratio of iron element to cobalt element in the mixture is 1:0.08; the concentration of gelatin in the first solution is 20wt%, and the mass ratio of gelatin, polyvinyl alcohol and metal salt in the first solution is 1:0.1:0.5; the concentration of divalent iron ions in the metal salt solution is 0.1mol / L; the first solution and the metal salt solution both contain ascorbic acid, and the molar ratio of ascorbic acid to iron element in the first solution and the metal salt solution is 0.1:1.
[0073] S2. Mix the iron source carrier, lithium acetate and phosphoric acid in water, adjust the pH to 2.2 to obtain a mixture, react the mixture in a reactor at 200° C. for 12 h, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0074] The molar ratio of P:Li:Fe+Co in the mixture is 1:1.3:1, and the concentration of lithium acetate in the mixture is 2.3 mol / L.
[0075] S3, grinding and mixing the lithium iron phosphate precursor and citric acid, spray drying, and calcining at 770° C. for 5 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0076] Among them, the mass of citric acid is 1.5% of the mass of the lithium iron phosphate precursor.
[0077] Example 3 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. In a nitrogen atmosphere, polyethylene glycol and ferrous chloride are mixed in an aqueous solution of tannic acid to form a first solution, the pH of the first solution is adjusted to 7.0, and the solution is allowed to stand to obtain a gel; the gel is placed in a 1 mol / L ferrous chloride solution at a solid-liquid ratio of 1 g:350 mL and immersed for 15 minutes to obtain an iron source carrier.
[0078] Among them, the concentration of tannic acid in the first solution is 28wt%, and the mass ratio of tannic acid, polyethylene glycol and ferrous chloride in the first solution is 1:0.26:0.1; the first solution and the ferrous chloride solution both contain ascorbic acid, and the molar ratio of ascorbic acid to the iron element in the first solution and the ferrous chloride solution is 0.3:1.
[0079] S2. Mix the iron source carrier, lithium chloride and phosphoric acid in water, adjust the pH to 5.8 to obtain a mixture, react the mixture in a reactor at 230° C. for 7 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0080] The molar ratio of P:Li:Fe in the mixture is 1:1.3:1, and the concentration of lithium chloride in the mixture is 0.8 mol / L.
[0081] S3. The lithium iron phosphate precursor and sucrose are mixed by sand grinding, spray drying, and then calcined at 530° C. for 13 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0082] Among them, the mass of sucrose is 0.3% of the mass of the lithium iron phosphate precursor.
[0083] Example 4 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the concentration of chitosan in the first solution is 1.5 wt %, and other conditions are exactly the same as those in Example 1.
[0084] Example 5 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the concentration of chitosan in the first solution is 2.8 wt %, and other conditions are exactly the same as those in Example 1.
[0085] Example 6 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the mass ratio of chitosan, polyethylene glycol and ferrous sulfate in the first solution is 1:0.09:0.3, and the other conditions are exactly the same as those in Example 1.
[0086] Example 7 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the mass ratio of chitosan, polyethylene glycol and ferrous sulfate in the first solution is 1:0.25:0.3, and the other conditions are exactly the same as those in Example 1.
[0087] Example 8 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the mass ratio of chitosan, polyethylene glycol and ferrous sulfate in the first solution is 1:0.2:0.15, and the other conditions are exactly the same as those in Example 1.
[0088] Example 9 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the mass ratio of chitosan, polyethylene glycol and ferrous sulfate in the first solution is 1:0.2:0.45, and the other conditions are exactly the same as those in Example 1.
[0089] Example 10 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the concentration of the ferrous sulfate solution is 0.5 mol / L, and the other conditions are exactly the same as those in Example 1.
[0090] Embodiment 11 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S1, the concentration of the ferrous sulfate solution is 0.8 mol / L, and the other conditions are exactly the same as those in Example 1.
[0091] Example 12 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S2, an iron source carrier, lithium hydroxide and phosphoric acid are mixed in water, and the pH is adjusted to 2.8 to obtain a mixture. Other conditions are exactly the same as those in Example 1.
[0092] Example 13 This embodiment provides a lithium iron phosphate positive electrode material. In the preparation method step S2, an iron source carrier, lithium hydroxide and phosphoric acid are mixed in water, and the pH is adjusted to 4.5 to obtain a mixture. Other conditions are exactly the same as those in Example 1.
[0093] Embodiment 14 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. In a nitrogen atmosphere, polyethylene glycol and ferrous sulfate are heated and mixed in an acetic acid aqueous solution of chitosan at 45° C. to form a first solution. The pH of the first solution is adjusted to 7.5, and the solution is allowed to stand to obtain an iron source carrier.
[0094] Among them, the concentration of acetic acid in the acetic acid aqueous solution is 1.5wt%, and the concentration of chitosan in the first solution is 2wt%; the mass ratio of chitosan, polyethylene glycol and ferrous sulfate in the first solution is 1:0.2:0.3; the first solution contains ascorbic acid, and the molar ratio of ascorbic acid to iron element in the first solution is 0.2:1.
[0095] S2. Mix the iron source carrier, lithium hydroxide, lithium fluoride and phosphoric acid in water, adjust the pH to 4.5 to obtain a mixture, react the mixture in a reactor at 180° C. for 16 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0096] The molar ratio of P:Li:Fe:F in the mixture is 1:1.3:1:0.01, and the concentration of lithium hydroxide in the mixture is 1.0 mol / L.
[0097] S3, grinding and mixing the lithium iron phosphate precursor and glucose, spray drying, and calcining at 650° C. for 7 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0098] Among them, the mass of glucose is 2.2% of the mass of the lithium iron phosphate precursor.
[0099] Comparative Example 1 This comparative example provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. Dissolve ferrous sulfate, lithium hydroxide and phosphoric acid in water to obtain a mixed solution, react the mixed solution in a reactor at 170° C. for 15 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0100] The molar ratio of P:Li:Fe in the mixed solution is 1:1.3:1; the concentration of lithium hydroxide in the mixed solution is 1.0 mol / L; the mixed solution also includes ascorbic acid, and the molar ratio of ascorbic acid to iron in the mixed solution is 0.2:1.
[0101] S2. The lithium iron phosphate precursor and glucose are sand-milled and mixed, spray-dried, and then calcined at 680° C. for 9 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0102] Among them, the mass of glucose is 2.2% of the mass of the lithium iron phosphate precursor.
[0103] Comparative Example 2 This comparative example provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. Dissolve ferrous sulfate, lithium hydroxide, polyethylene glycol and phosphoric acid in water to obtain a mixed solution, react the mixed solution in a reactor at 170° C. for 15 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0104] The molar ratio of P:Li:Fe in the mixed solution is 1:1.3:1; the concentration of lithium hydroxide in the mixed solution is 1.0 mol / L; the mass ratio of polyethylene glycol to ferrous sulfate is 0.2:0.5. The mixed solution also includes ascorbic acid, and the molar ratio of ascorbic acid to iron in the mixed solution is 0.2:1.
[0105] S2. The lithium iron phosphate precursor and glucose are sand-milled and mixed, spray-dried, and then calcined at 680° C. for 9 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0106] Among them, the mass of glucose is 2.2% of the mass of the lithium iron phosphate precursor.
[0107] Comparative Example 3 This comparative example provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. In a nitrogen atmosphere, heat ferrous sulfate in an acetic acid aqueous solution of chitosan at 45°C to form a first solution, adjust the pH of the first solution to 7.5, and allow to stand to obtain a gel; soak the gel in a 0.3 mol / L ferrous sulfate solution at a solid-liquid ratio of 1 g:200 mL for 10 minutes to obtain an iron source carrier.
[0108] Among them, the concentration of acetic acid in the acetic acid aqueous solution is 1.5wt%, and the concentration of chitosan in the first solution is 2wt%; the mass ratio of chitosan to ferrous sulfate in the first solution is 1:0.3; the first solution and the ferrous sulfate solution contain ascorbic acid, and the molar ratio of ascorbic acid to the iron element in the first solution and the ferrous sulfate solution is 0.2:1.
[0109] S2. Mix the iron source carrier, lithium hydroxide, phosphoric acid and polyethylene glycol in water, adjust the pH to 4.5 to obtain a mixture, react the mixture in a reactor at 170° C. for 15 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0110] The molar ratio of P:Li:Fe in the mixture is 1:1.3:1, the concentration of lithium hydroxide in the mixture is 1.0 mol / L; the mass ratio of polyethylene glycol to ferrous sulfate is 0.2:0.5.
[0111] S3, grinding and mixing the lithium iron phosphate precursor and glucose, spray drying, and calcining at 680° C. for 9 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0112] Among them, the mass of glucose is 2.2% of the mass of the lithium iron phosphate precursor.
[0113] Comparative Example 4 This comparative example provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: S1. Mix and dissolve chitosan and polyethylene glycol in water under a nitrogen atmosphere to obtain a first solution, and adjust the pH of the first solution to 7.5 to obtain a gel.
[0114] The concentration of chitosan in the first solution is 2 wt %, and the mass ratio of chitosan to polyethylene glycol is 1:0.2.
[0115] S2. Mix the gel, ferrous sulfate, lithium hydroxide and phosphoric acid in water, adjust the pH to 4.5 to obtain a mixture, react in a reactor at 160° C. for 15 hours, filter, wash and dry to obtain a lithium iron phosphate precursor.
[0116] The molar ratio of P:Li:Fe in the mixture is 1:1.3:1, the concentration of lithium hydroxide in the mixture is 1.0 mol / L, and the mass ratio of polyethylene glycol to ferrous sulfate in the mixture is 0.2:0.5.
[0117] S3, grinding and mixing the lithium iron phosphate precursor and glucose, spray drying, and calcining at 680° C. for 9 h in a nitrogen atmosphere to obtain a lithium iron phosphate positive electrode material.
[0118] Among them, the mass of glucose is 2.2% of the mass of the lithium iron phosphate precursor.
[0119] The present invention tests the crystal structure and related parameters of the lithium iron phosphate positive electrode materials provided in Examples 1-14 and Comparative Examples 1-4 (as shown in Table 1), and simultaneously measures their physical properties and the electrochemical properties of the corresponding lithium batteries (as shown in Tables 1 and 2). The specific steps are as follows: (1) X-ray diffraction (XRD) test The XRD pattern was obtained by testing the crystal phase and crystal structure of the lithium iron phosphate cathode material using an X-ray powder diffractometer (Rigku Ultima IV). The diffraction source used in the test was Cu-Ka, the wavelength λ=0.15406nm, the step length was 0.02°, and the scanning speed was 2° / min. GSAS-Ⅱ was used to refine the crystal structure of the obtained XRD pattern to obtain an X-ray diffraction pattern. The R wp (Weighted Graphical Variance Factor) ≤ 5%.
[0120] The percentage of iron-lithium antisite defects was calculated using GSAS-Ⅱ software ( , (200) and (020) characteristic diffraction peaks ( )、Half peak width( ) and peak intensity, the peak intensity of the (200) and (020) characteristic diffraction peaks is deducted from the peak intensity of the background diffraction peak to obtain the peak intensities of the actual characteristic diffraction peaks, which are I (200) and I (020) The grain size in the direction of the (020) characteristic diffraction peak crystal plane is calculated using the Scherrer formula. ; k is a constant value, the value is 0.9; refers to the wavelength of the incident ray, λ=0.15406 nm; is the half-peak width of the characteristic diffraction peak, in rad; It refers to the diffraction angle, and the unit is °. The test results of Example 6 are as follows Figure 1 shown.
[0121] (2) Transmission electron microscopy (TEM) test The morphology of the lithium iron phosphate cathode material was analyzed using TEM of JEM-2000EX. The test results of Example 7 are as follows: Figure 2 As shown. Figure 2 It can be seen that the lithium iron phosphate positive electrode material prepared in Example 7 has a spherical morphology, and the surface is covered with a carbon layer. The interplanar spacing at a higher resolution shows that the lithium iron phosphate crystals grow along the ac plane direction.
[0122] (3) Tap density test The tap density of lithium iron phosphate positive electrode material is tested according to the test standard GB / T 21354-2008.
[0123] (4) Electrochemical performance test The lithium iron phosphate positive electrode material obtained above was assembled into a button cell for electrochemical performance testing, and the specific steps were as follows: the lithium iron phosphate positive electrode material, acetylene black and polyvinylidene fluoride were uniformly mixed in N-methylpyrrolidone at a mass ratio of 90:5:5, and then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, a positive electrode sheet with a diameter of 12 mm was pressed into a sheet press in an argon glove box. In the glove box, the positive electrode sheet, polypropylene porous diaphragm, negative lithium sheet and electrolyte were assembled into a button cell, and the electrolyte was 1M LiPF6-EC:DMC (volume ratio 1:1), and the electrochemical performance was tested.
[0124] (4-1) Cyclic voltammetry test The button cell was subjected to cyclic voltammetry test using a CHI660E electrochemical workstation to investigate the reaction kinetics of the lithium iron phosphate electrode material. The test voltage window was 2.4V-4.2V and the test temperature was -15°C.
[0125] In the tested voltage range, the lithium ions of the electrode material begin to deintercalate due to the redox reaction, showing a pair of redox peaks, and a cyclic voltammetry (CV) curve is obtained. The peak position and peak potential value of the redox peak in the cyclic voltammetry (CV) curve can reflect the phase change and ion diffusion process in the lithium iron phosphate electrode material, and the potential difference between the oxidation peak and the reduction peak can reflect the polarization degree of the electrode and the diffusion degree of lithium ions. The smaller the potential difference between the oxidation peak and the reduction peak, the lower the polarization degree and the higher the lithium ion diffusion capacity of the electrode, and the better the electrode reaction kinetics. Furthermore, the growth rate of the potential difference between the oxidation peak and the reduction peak at different scan rates can reflect whether the diffusion transfer of lithium ions is rapid and whether the deintercalation is sufficient during high-rate charge and discharge. The smaller the growth rate of the potential difference, the more stable the diffusion capacity of lithium ions remains during charge and discharge at different rates, and the less the polarization degree will increase significantly, which directly affects the low-temperature performance and rate performance of lithium-ion batteries.
[0126] The cyclic voltammetry curves of Example 6 and Comparative Example 2 are as follows: Figure 3 As shown, with the continuous increase of the scan rate, the cyclic voltammetry curve of Comparative Example 2 gradually deforms, and the potential difference between the oxidation peak and the reduction peak increases significantly, while the shape of the cyclic voltammetry curve of Example 6 remains stable.
[0127] Testing method for the growth rate T of the redox peak potential difference: sequentially test the redox peak potential difference of the lithium iron phosphate electrode material at different scanning rates L (0.2 mV / s, 0.6 mV / s, 1.0 mV / s), and use the following formula to calculate the growth rate T of the redox peak potential difference.
[0128] T1 , T2 Among them, L 0.2 represents the potential difference of the redox peak of lithium iron phosphate electrode material at a scanning rate of 0.2mV / s, L 0.6 represents the potential difference of the redox peak of lithium iron phosphate electrode material at a scanning rate of 0.6 mV / s, L 1.0 Represents the potential difference of the redox peak of lithium iron phosphate electrode material at a scan rate of 1.0mV / s.
[0129] (4-2) Constant current charge and discharge test The LAND battery test system was used to perform constant current charge and discharge tests on button cells to examine the electrochemical properties of lithium iron phosphate cathode materials, such as rate performance and capacity retention. The test voltage was 2.0V-3.9V. For 1 gram of lithium iron phosphate cathode material, the 1C charge and discharge rate was 170 mA.
[0130] Among them, the discharge specific capacity at different rates was tested at room temperature 25°C; the low-temperature capacity retention rate was tested at 1C, and the calculation formula is: ×100%.
[0131] Example 6 is used as an example to illustrate the calculation process of crystal structure degree and related parameters. Figure 1 As shown, Y obs is the observed data of XRD, Y calc Y is the calculated data after the observation data is refined. diff is the difference curve between the observed data and the calculated data, GOF is the goodness of fit factor, R wp is the refined weighted graph variance factor. The present invention obtains Fe based on the refined calculation data analysis and calculation Li 1.53%, I (200) is 7323.83 and I (020) The diffraction angle of the (020) characteristic diffraction peak is 18579.56. The half-peak width is 14.8642° and 0.00227 rad. According to the Scherrer formula, D (020) It is 62.9nm.
[0132] Table 1 Crystal structure degree α and related parameters of different embodiments and comparative examples Tap density test results
[0133] Table 2 Electrochemical performance test results of different embodiments and comparative examples
[0134] Combining Table 1 and Table 2, when the crystal structure degree α value is 0.15nm -1 -4.5nm -1 When the lithium iron phosphate cathode material has good electrode reaction kinetics, that is, the reaction activation energy required for lithium ion extraction and insertion is low, and the lithium ion diffusion rate is fast. Therefore, it has a low growth rate of redox peak potential difference at different scanning rates at low temperature (-15°C), and the corresponding lithium ion battery has both excellent rate performance and low temperature resistance. Furthermore, when the crystal structure α value is 0.5nm -1 -1.1nm -1 When the redox peak potential difference at low temperature (-15°C) is increased, the growth rate is smaller, and the corresponding rate performance and low temperature resistance of the lithium-ion battery are better.
[0135] Comparative Examples 2, 4 and 10, D (020) and There is little difference, but the Fe in Example 10 Li(1.95%) was the highest, while Example 2 and Example 4 were 1.63% and 1.1% respectively. (020) In the approximate case, Fe Li The lower the value, the less obstruction the lithium ion diffusion channel encounters, and vice versa. Li Minimum, α is 0.6933 nm -1 , indicating that lithium ion diffusion is better, and lithium ions can be fully and quickly transmitted at 5C rate and low temperature, thus having excellent rate performance (5C / 1C: 86.22%), low temperature capacity retention rate and low redox potential difference growth rate (low polarization degree). It can be seen from the experimental data that with the increase of Fe Li becomes larger, α increases accordingly, the rate performance and low temperature performance of the lithium-ion battery decrease, and the degree of polarization increases.
[0136] Comparative Examples 3, 5 and 11, Fe Li and The difference is not big, D of Example 11 (020) The minimum is 47.1nm, and Examples 3 and 5 are 70.4nm and 56.5nm respectively. Li and In the approximate case, with D (020) As α increases, α decreases. At 0.1C, the discharge capacity of the lithium iron phosphate cathode material increases in turn. This is because D (020) Will affect the grain size of the material, D (020) The larger the value, the larger the grain size of the material, thereby increasing the tap density of the material and helping to increase the specific capacity. (020) The increase of D in Example 11 makes the lithium ion diffusion channel longer, resulting in that the rate performance and low temperature capacity retention rate of Example 3 are lower than those of Example 5, and the growth rate of the redox potential difference is higher than that of Example 5. (020) Shortest, but with similar Fe Li , so that its unit D (020) The greater degree of dimensional hindrance results in Example 11 and Example 5 having similar rate performance, low temperature resistance and polarization degree.
[0137] Comparative Examples 6, 12 and 14, Fe Li and D (020) The difference is not big, indicating that their lithium ion diffusion channels are not only similar in length but also have the same degree of obstruction. is obviously different. The smaller it is, the higher the degree of preferential orientation. The morphology of the lithium iron phosphate positive electrode material tends to be plate-like or even flaky, which causes its tap density to decrease, and thus the discharge specific capacity to decrease, but the low temperature resistance, rate performance and polarization degree are not much different.
[0138] Comparative Example 2 and D (020) All are within the range set by the present invention, but the Fe Li The crystal structure degree α is too large, which is 5.2367 nm. -1 Although Comparative Example 2 has a shorter lithium ion diffusion channel (42.1 nm), Fe Li If it is too large, the lithium ion diffusion channel will be hindered, which will in turn affect the electrochemical performance of the lithium ion battery.
[0139] The crystal structure degree α value of comparative example 3 is 0.1460 nm -1 It is not within the range set by the present invention. It can be seen from the table that comparative example 3 has a lower Fe Li (0.62%) and short lithium ion diffusion channels (64.8nm), but too low The lithium iron phosphate positive electrode material has a flaky morphology, resulting in the lowest tap density of the material, and thus the lowest discharge specific capacity at 0.1C.
[0140] Although the Fe Li , D (020) and All of them are within the set range of the present invention, but the value of the crystal structure degree α is 4.6139 nm -1 If the range set by the invention is not met, excellent rate performance, low temperature resistance and polarization degree cannot be achieved.
[0141] Adjusting the reaction parameters of steps S1 and S2 can regulate the crystal structure of lithium iron phosphate cathode materials, thereby regulating the crystal structure degree. , to affect the physical and electrochemical properties of the lithium iron phosphate positive electrode material. Specifically, preparing an iron source carrier with different sustained-release properties in step S1 can affect the crystal structure of the lithium iron phosphate positive electrode material. The content of any one of the macromolecules, crystal form regulators and metal salts in the first solution will affect the cross-linking state of the gel. The higher the content, the greater the cross-linking density in the gel, the tighter and stronger the network structure of the gel, and the increased mechanical strength. The mechanical strength will affect the sustained-release effect of the iron source carrier. The higher the mechanical strength, the higher the Fe 2+ and the crystal form modifier are released more slowly in the hydrothermal reaction. The less, the The higher the mechanical strength, the lower the Fe 2+ and the crystal form modifier are released faster in the hydrothermal reaction. The more, at the same time The lower.
[0142] The content of crystal form regulator in the iron source carrier will also affect the morphology of the lithium iron phosphate cathode material. The higher the content of crystal form regulator, the easier it is for the lithium iron phosphate cathode material to be preferentially oriented, and the morphology tends to be plate-like or even flaky, resulting in a lower tap density of the lithium iron phosphate cathode material, thereby reducing the corresponding lithium ion battery discharge capacity. In addition, the concentration of the metal salt solution will also affect the release effect of the iron source carrier. The gel is placed in a metal salt solution and immersed in the load. The higher the concentration of the metal salt solution, the more Fe is loaded per unit volume of gel. 2+ The more Fe is released per unit time in the hydrothermal reaction, the 2+ The more, the higher the local ion concentration, the faster the reaction rate, the faster the crystal nucleation rate is than the growth rate, D (020) The grain size becomes smaller, Increase.
[0143] In step S2, the pH of the hydrothermal reaction system affects the release of the iron source carrier, thereby affecting the crystal structure of the lithium iron phosphate positive electrode material. The lower the pH of the hydrothermal reaction system, the faster the iron source carrier dissolves, making the lithium iron phosphate positive electrode material The pH of the hydrothermal reaction system is high, and the iron source carrier dissolves slowly, which makes the lithium iron phosphate cathode material At the same time, the ion reaction rate is slow, and the crystal is more inclined to grow. (020) The grain size becomes larger. Since the iron source carrier dissolves slowly, there is a large difference in the speed of formation of lithium iron phosphate particles, which naturally produces a grading effect, making the lithium iron phosphate positive electrode material have a high tap density and high discharge specific capacity.
[0144] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely illustrative, and embodiments having substantially the same structure as the technical idea and exerting the same effects within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments, and other methods of combining some of the constituent elements in the embodiments to construct are also included in the scope of the present application.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: It includes a lithium iron phosphate matrix and a carbon coating layer located on the surface of the lithium iron phosphate matrix; the crystal structure of the lithium iron phosphate positive electrode material ×10000, unit is nm -1 , α satisfies 0.15nm -1 ≤α≤4.5nm -1 , In the formula, represents the percentage of lithium iron antisite defects in the lithium iron phosphate positive electrode material, D (020) represents the grain size of the (020) crystal plane of the lithium iron phosphate positive electrode material, in nm. I (200) represents the peak intensity of the (200) characteristic diffraction peak in the X-ray diffraction spectrum of the lithium iron phosphate positive electrode material, I (020) It represents the peak intensity of the (020) characteristic diffraction peak in the X-ray diffraction spectrum of the lithium iron phosphate positive electrode material.
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium iron phosphate positive electrode material satisfies at least one of the following characteristics (1)-(4): Feature (1): The crystal structure degree α of the lithium iron phosphate positive electrode material satisfies 0.5nm -1 ≤α≤1.1nm -1 ; Feature (2): The lithium iron phosphate positive electrode material ≤5%; Feature (3): D of the lithium iron phosphate positive electrode material (020) The value ranges from 35nm to 85nm; Feature (4): The lithium iron phosphate positive electrode material The value is 0.25-0.
45.
3. The lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The general structural formula of the lithium iron phosphate matrix is Li 1-x J x Fe 1-y M y (PO 4-z )Q z ; Wherein, J is selected from at least one of Na and Mg; M is at least one selected from Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; Q is selected from at least one of F, S, N and Cl; 0≤x≤0.1, 0≤y≤0.1 and 0≤z≤0.
1.
4. A method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: Mixing a crystal form regulator and a metal salt in a macromolecular solution to form a first solution, adjusting the pH of the first solution to obtain a gel; and soaking the gel in a solution of the metal salt to obtain an iron source carrier; The iron source carrier, the lithium source and the phosphorus source are mixed in water to obtain a mixture; the mixture is subjected to a hydrothermal reaction and solid-liquid separation to obtain a lithium iron phosphate precursor; The lithium iron phosphate precursor and the carbon source are mixed and calcined under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.
5. The preparation method according to claim 4, characterized in that: The metal salt includes an iron salt and an M salt, wherein the molar ratio of the iron element in the iron salt to the M element in the M salt is 1:0-0.11, The iron salt is a soluble salt of divalent iron, including at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate and ferrous acetate. The M salt is a water-soluble salt of the M element, and the M element includes at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y.
6. The preparation method according to claim 4 or 5, characterized in that: The process for preparing the iron source carrier satisfies at least one of the following features (5)-(11): Feature (5): The percentage content of the macromolecule in the first solution is 1wt%-30wt%; Feature (6): The mass ratio of the macromolecule, the crystal form regulator and the metal salt in the first solution is 1:0.05-0.3:0.05-0.5; Feature (7): The macromolecule comprises at least one of chitosan, carboxymethyl chitosan, tannic acid, gelatin and aminoethyl-β-cyclodextrin, and the crystal form regulator comprises at least one of ethylene glycol, polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and diethylene glycol; Feature (8): The pH adjustment refers to adjusting the pH of the first solution to 7.0-7.5; Feature (9): The concentration of divalent iron ions in the metal salt solution is 0.1 mol / L-1.0 mol / L; Feature (10): The solid-to-liquid ratio of the gel and the metal salt solution is 1 g: 100 mL-500 mL, and the soaking time is 10 min-30 min; Feature (11): The first solution and / or the metal salt solution also includes an antioxidant, the antioxidant includes ascorbic acid, and the molar ratio of the antioxidant to the iron element in the first solution and / or the metal salt solution is 0.1-0.3:
1.
7. The preparation method according to claim 4 or 5, characterized in that: The preparation method satisfies at least one of the following features (12) to (15): Feature (12): The lithium source comprises at least one of lithium hydroxide, lithium chloride and lithium acetate, and the concentration of the lithium source in the mixture is 0.8 mol / L-2.5 mol / L; Feature (13): The mixture further includes a doping source, which includes a metal doping source and / or a non-metal doping source; the metal doping source is a J source, which is a water-soluble compound containing at least one of the elements Na and Mg; the non-metal doping source is a Q source, which is a water-soluble compound containing at least one of the elements F, S, N and Cl; Feature (14): The pH of the mixture is 2.0-6.0; Feature (15): The reaction temperature of the hydrothermal reaction is 140°C-240°C, and the reaction time is 5h-20h.
8. The preparation method according to claim 4 or 5, characterized in that: The preparation method satisfies at least one of the following features (16) to (18): Feature (16): The carbon source comprises at least one of sucrose, glucose, starch, polyethylene glycol, phenolic resin, cellulose and citric acid, and the mass of the carbon source is 0.1%-3% of the mass of the lithium iron phosphate precursor; Feature (17): The inert atmosphere comprises at least one of nitrogen, helium and argon; Feature (18): The calcination temperature is 500°C-800°C, and the calcination time is 4h-14h.
9. A positive electrode sheet, characterized in that: The invention comprises the lithium iron phosphate positive electrode material as described in any one of claims 1 to 3 or the lithium iron phosphate positive electrode material prepared by the preparation method as described in any one of claims 4 to 8.
10. A lithium battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Lithium iron phosphate composite positive electrode material, preparation method thereof, lithium-ion battery and capacitor
CN110277541A
Carbon composite lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN114335517A
Active material for secondary battery electrode and secondary battery using same
CN114930580A
High Voltage Lithium Ion Positive Electrode Material with Improved Cycle Life
US20120208067A1
Cited By
Organic framework in-situ derived low-energy-gap lithium iron phosphate material and application thereof
CN120709334A
Lithium iron phosphate positive electrode material and preparation method therefor, positive electrode sheet, and lithium battery
WO2026188821A1